Pretreatment absolute lymphocyte count is an independent predictor for survival outcomes for esophageal squamous cell carcinoma patients treated with neoadjuvant chemoradiotherapy and pembrolizumab: An analysis from a prospective cohort - Wei‐Xiang Qi; Xiaoyan Wang; Chengqiang Li; Shuyan Li; Huan Li; Feifei Xu; Jiayi Chen; Shengguang Zhao; Hecheng Li (Thoracic Cancer, 2023)
Abstract Background The aim of the study was to analyze the relationship between pretreatment inflammatory biomarkers (IBs) and survival outcomes for patients with esophageal squamous cell carcinoma (ESCC) treated with neoadjuvant chemoradiotherapy (neo‐CRT) and pembrolizumab. Methods Clinical variables and IBs (absolute monocyte count [AMC], absolute lymphocyte count [ALC], platelet count [PLT], neutrophil‐to‐lymphocyte ratio [NLR], platelet‐to‐lymphocyte ratio [PLR], lymphocyte‐to‐monocyte ratio [LMR], pan‐immune inflammation value [PIV], systemic immunoinflammatory index [SII], systemic immunoreactivity index [SIRI] and prognostic nutritional index [PNI]) were collected. Univariate and multivariate analysis were performed to identify the independent factors for outcomes of ESCC. Results A total of 51 patients were included. Of these, 35 patients achieved pathological complete response (pCR) after neo‐CRT and pembrolizumab (pCR: 68.6%). With a median follow‐up of 20 months, the two‐year PFS and OS of the cohort was 64% and 91%, respectively. Multivariate logistic regression analysis indicated that ALC (overall response [OR] 4.4, p = 0.051) and PLT (OR 6.7, p = 0.023) were two independent predictors for achieving pCR among ESCC treated with neo‐CRT and pembrolizumab. Multivariate Cox regression analysis showed that ALC (HR 0.27, p = 0.028) and SIRI (HR 3.13, p = 0.048) were two independent predictors associated with PFS. Kaplan Meier analysis demonstrated that the PFS of ESCC with high baseline ALC was significantly better than those with low ALC (2‐year PFS: 77% vs. 47%, p = 0.027), but not for overall survival (2‐year OS: 96% vs. 87%, p = 0.46). Conclusions This retrospective analysis based on a prospective cohort for the first time demonstrates that pretreatment ALC is an independent predictor for achieving pCR and favorable outcomes of ESCC treated with neo‐CRT and pembrolizumab.